Monitoring and recovery of hyperglycaemia-induced endothelial dysfunction with rheopheresis in diabetic lower extremity ulceration with hyperviscosity. (9th November 2022) - Gál, Kristóf; Asbóth, Georgina; Vass, Melinda; Bíró, Attila; Markovich, Arnold; Homoki, Judit; Fidler, Gábor; Paholcsek, Melinda; Cziáky, Zoltán; Németh, Norbert; Remenyik, Judit; Soltész, Pál
Aims: Rheopheresis is an extracorporeal haematotherapy that improves haemorheological status by filtering proteins that enhance blood viscosity. It also has anti-inflammatory effects by removing inflammatory cytokines. Our study aims to examine the effects of rheopheresis on the endothelial status in diabetic lower extremity ulceration. Methods: In vitro experiments were performed in a HUVEC model to mimic hyperglycaemic stress. We determined the changes in gene expression levels of IL-6, IL-8, TNF-alpha, endothelin convertase enzyme, ET-1, and NO synthase, as well as the ROS and intracellular GSH levels upon hyperglycaemia. In in vivo studies, two rheopheresis procedures were performed on seven patients with diabetic lower extremity ulceration with hyperviscosity, and we measured the changes in plasma concentrations of ET-1, TXB2, SOD enzyme activity, and extracellular components of the glutathione pool depending on treatments. Results: Our results showed that hyperglycaemia increases endothelial expression of inflammatory cytokines, ET-1, and endothelin convertase enzyme, while NO synthase was decreased. As a result of rheopheresis, we observed decreased ET-1 and TXB2 concentrations in the plasma and beneficial changes in the parameters of the glutathione pool. Conclusion: To summarize our results, hyperglycaemia-induced oxidative stress and endothelial inflammation can be moderated by rheopheresis in diabetic lower extremity ulceration with hyperviscosity.